MASOFAVIY ESP TA’LIMDA MULTIMODAL SUN’IY INTELLEKT INTEGRATSIYASI ORQALI VIZUAL VA AUDIAL YONDASHUV ASOSIDA KONTEKSTUAL OG‘ZAKI NUTQNI RIVOJLANTIRISH (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
This thesis addresses the development of contextual oral communication in distance ESP instruction through the integration of multimodal artificial intelligence technologies. The study substantiates that harmonizing visual and auditory modalities enhances learners’ communicative competence. Using AI tools—ChatGPT, Whisper, D-ID, and related platforms—an interactive, reflective, and learner-centred instructional environment was designed. The multimodal approach is recommended as an effective methodological direction for improving spoken production in ESP.